Women-Rabbi Fiction in the 21st Century: An Update - Zucker, David J. (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
Women rabbis have been depicted in fiction for close to fifty years. In the second decade and then in the beginning of the third decade of the twenty-first century over a dozen fictional women rabbis appear as central or important characters in novels, short stories, and on the silver screen. Most of them make their first appearance. This article takes note of the authors of these works, and then looks at the characters themselves, contrasting their “fictional” experiences with the published experiences of “real-life” women rabbis. It discusses these fictional women rabbis in terms of their theology/sense of tradition; religious/educational backgrounds; gender identification; and where that information is dealt with in the storyline, how these women address some of the challenges facing women rabbis such as dressed for success; pay inequity; and matters of sexual harassment. This is followed by a section on how women regard success in the rabbinate. A caveat: the real-lived experiences of women rabbis, their definitions of success and their joys/concerns/issues/disquiets are not necessarily the subjects that concern writers of fiction that feature women rabbis as characters.